Indonesia in the New World : Globalisation, Nationalism and Sovereignty - Basri, M. Chatib; Pangestu, Mari; Patunru, Arianto Arif, 1972- (Book collections on Project MUSE., 2018)
Globalisation is more complex than ever. The effects of the global financial crisis and increased inequality have spurred anti-globalisation sentiment in many countries and encouraged the adoption of populist and inward-looking policies. This has led to some surprising results: Duterte, Brexit and Trump, to name a few. In Indonesia, the disappointment with globalisation has led to rising protectionism, a rejection of foreign interference in the name of nationalism, and economic policies dominated by calls for self-sufficiency. Meanwhile, human trafficking and the abuse of migrant workers show the dark side of globalisation. In this volume, leading experts explore key issues around globalisation, nationalism and sovereignty in Indonesia. Topics include the history of Indonesia's engagement with the world, Indonesia's stance on the South China Sea and the re-emergence of nationalism. The book also examines the impact of globalisation on poverty and inequality, labour markets and people, especially women.